Estimation of annual rate and spatial distribution of soil erosion in the Jamuna basin using RUSLE model: A geospatial approach - Monojit Saha; Samrin Sumaiya Sauda; H. Rainak Khan Real; Mallik Mahmud (Environmental Challenges, 2022)
Soil erosion poses a serious threat to the western Jamuna sub-basin area in Bangladesh, comprising of 8 districts and 202 unions. The Revised Universal Soil Loss Equation (RUSLE) methodology integrated with Remote Sensing and Geographic Information System (GIS) was applied to compute the annual soil erosion rate for the western Jamuna sub-basin area. Primarily open-source data was utilized in this study to propose a low-cost and rapid soil erosion monitoring framework. Results indicate that a total of 598,232 tons of soil is being lost annually from the study area. Furthermore, the study estimates a potential average soil erosion rate of approximately 29.5 tons/ha/year in the 202 unions. The spatial distribution of soil erosion suggests that the unions of Bogra, Sirajganj and Jamalpur districts undergo higher soil loss compared to the unions of Pabna and Natore districts. The three unions with dominant mean soil erosion rates are the Bhandarbari and the Sariakandi Paurashava of Bogra district, and the Kaoakola union of the Sirajganj district. Heavy rainfall after a prolonged dry season, the presence of steep slopes and the susceptibility of the unions located in proximity to the Bangali river and the Jamuna river leading to higher rates of surface runoff and floods resulted in higher rates of soil erosion. On the contrary, the Atgharia Paurashava and Debottar unions of Pabna district and the Moshinda union of Natore district are the unions with minimal soil erosion rates, which likely be attributed to the presence of flat terrain, low annual rainfall, higher vegetation cover and the predominance of clayey soils. Overall, the study identifies an increasing trend of soil erosion rates from the south-western part of the study area towards the central, north-eastern and south-eastern parts which are close to the Jamuna river. Such quantification of annual soil loss is necessary for the formulation and implementation of effective soil conservation strategies.